2017
DOI: 10.1002/cncr.31052
|View full text |Cite
|
Sign up to set email alerts
|

Distrust in health care and cultural factors are associated with uptake of colorectal cancer screening in Hispanic and Asian Americans

Abstract: Correlations between CRC screening and associated factors differ among HAs and AAs, suggesting a need for multilevel interventions tailored to race/ethnicity. The current findings suggest that facilitating access to care without improving perceived quality of health services may be ineffective for increasing the uptake of CRC screening among HAs and AAs. Cancer 2018;124:335-45. © 2017 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 42 publications
1
21
1
Order By: Relevance
“…However, there is some suggestion that education attainment might not be as salient a marker of social status for Latinos when compared to years in the U.S. or employment status (Ostrove et al 2000). Further, upward social mobility correlated with more years of living in the U.S., but not satisfaction with care, which aligns with previous research that associates exposure to negative experiences related to ethnicity or race in U.S. health care settings (Hong el al 2017). Stable social mobility was associated with greater age and fewer years of education, factors that should be addressed further in their implications for treatment expectations and experiences.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…However, there is some suggestion that education attainment might not be as salient a marker of social status for Latinos when compared to years in the U.S. or employment status (Ostrove et al 2000). Further, upward social mobility correlated with more years of living in the U.S., but not satisfaction with care, which aligns with previous research that associates exposure to negative experiences related to ethnicity or race in U.S. health care settings (Hong el al 2017). Stable social mobility was associated with greater age and fewer years of education, factors that should be addressed further in their implications for treatment expectations and experiences.…”
Section: Discussionsupporting
confidence: 86%
“…For example, blocked opportunities for upward social mobility may create difficulties in accessing health services and receiving quality health care. Of note, among Latinos higher acculturation scores and greater English language skills are associated with greater medical mistrust; one explanation for this observation is that increased experiences with health care services may also increase negative experiences related to ethnicity or race in these settings (Hong et al 2017). Nevertheless, greater quality of care can be a mediating factor as it is associated with higher rates of health screenings regardless of levels of acculturation or years living in the United States (Hong et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, in the nature of secondary data analysis, we were able to examine only available information in the dataset. It has been reported that interventions of self-management for a single chronic condition may have a spillover effect to improve management of other conditions ( Foster et al, 2007 ) and improved interaction quality with health care providers are positively associated with the uptake of CRC screening ( Hong et al, 2018 ). Further studies should explore and examine other possible, unintended positive effects of factors, aside from socioeconomic determinants, on patient health behavior and associated outcomes among those with T2DM.…”
Section: Limitationsmentioning
confidence: 99%
“…[12][13][14] Better communication and interactions between patients and providers promote effective coping strategies and self management required for those with diabetes. 12,[15][16][17][18][19][20][21][22][23] In this regard, the teach-back method could be promising to improve the relationship and close the loop in diabetic patient care.…”
Section: Introductionmentioning
confidence: 99%